Clinical Evaluation of Perhexiline Maleate in Patients with Angina Pectoris. Issue 5787 (4th December 1971) - Burns-Cox, C. J.; Chandrasekhar, K. P.; Ikram, H.; Peirce, T. H.; Pilcher, J.; Quinlan, C. D. M.; Rees, J. Russell
Abstract : This paper reports a double-blind trial of a new antianginal drug, perhexiline. Fifty-five patients suffering from angina pectoris were studied for periods of 12 or 24 weeks in a cross-over comparison against a placebo in four centres in the United Kingdom and Ireland. Perhexiline was effective in most patients as judged by reducing the number of anginal attacks in 84% and the consumption of glyceryl trinitrate tablets in 64%. The major side effect, dizziness, noted in one-third of the patients, may be dose/body-weight related. Perhexiline is a valuable new agent for the treatment of patients with angina, especially those who do not respond to other antianginal agents.